PROBLEMS FACE BY VOCATIONAL HIGH SCHOOL STUDENTS IN LEARNING ENGLISH AT SMK NEGERI KEBONAGUNG - Samsul Hadi; Oktavia Intan Permatasari; Siska Nurma Yuniar; Widha Wannisa (English Education Study Program STKIP PGRI Pacitan, 2023)
Learning English is very important especially for education and future, this is because English is one of the international languages ​​used. This case study aims to analyze the difficulties of learning English in grade 10 students at the vocational high school level. This research is mainly to find the students' difficulties in mastering English. This research was conducted at SMK Negeri Kebonagung involving 70 students as subjects. Researchers used a classical and individual approach in collecting data. The data was obtained using a google form which was distributed to 70 students of class x in various majors. The findings show that students' English learning difficulties are: (1) a sense of coercion; (2) mastery of basic concepts/low intake; (3) lack of self-confidence; (4) forgetting factor; (5) have little opportunity to practice. Referring to these findings, it is suggested to teachers and institutions to facilitate and provide high motivation for the students' English learning process.